The emergence of cultural content in the professional development of in-service teachers of Spanish - Llanes Sanchez, Juliana Patricia (Working Papers in Language Pedagogy, 2016)
The use of literature to teach culture has been widely accepted in the field of foreign language teaching. As a result, literature continues to appear in language teacher training syllabi and theoretical proposals regularly refer to literature as a language laboratory where intercultural skills can be developed (Cuq & Gruca, 2003). The current case study explores a world literature PhD course at a university in Budapest, belonging to the professional development of in-service teachers of Spanish as a foreign language. The study attempts to identify what type of cultural content arises in this PhD course. Participant observations, audio recordings, interviews and the researcher’s journal were used as instruments for data collection. The outcomes suggest that the emerging cultural content refers to cultural products, cultural practices and cultural competence. The findings also show that cultural content is linked to multidimensional views of culture and to the consideration of classroom culture as a resource to meet different cultural practices and to develop course participants’ cultural competence. Limitations and pedagogical implications are also outlined at the end of the paper.